Penerapan Model Think Talk Write (TTW) Untuk Meningkatkan Keterampilan Menulis Narasi Di Kelas Tinggi - Rani Febyani Febyani; Dyah Lyesmaya; Iis Nurasiah (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Research through the Think talk Write Model (TTW) aims to improve student narrative writing skills in elementary school high grade. The type of research used is class action research (PTK). The number of students examined in this study was 39 people comprised of 17 male 22 women. Data collection tools using tests and observation sheets. Results showed the value of writing narrative skills on pre-cycle activities gained an average percentage of 33% with low categories, on cycle I gained an average percentage of 69% with sufficient categories, then in Cycle II gained Average percentage of 87% with good categories while the teacher activity cycle I gained an average value of 58% with sufficient categories, II cycle gained a value of 79% with good category and student activity Cycle I gained an average value of 66% with category Enough, cycle II earns a value of 79% with good categories. The study concluded that implementing a TTW model could improve the narrative writing skills of class V at SDN Cinggah 2 in Sukabumi school year 2018/2019